Pengaruh Teknologi Informasi, Pemanfaatan Teknologi Informasi, Efektivitas Penggunaan Dan Kepercayaan Teknologi Informasi Terhadap Kinerja Individual(Survei Pada Kantor Pelayanan Pajak Pratama Sukoharjo) - Sawitri, Sawitri, Dr. Noer Sasongko, SE., Ak., M.Si (2016)
This research aims to analyze the influence of information technology, utilization of information technology, usage effectiveness, and confidence in information technology on individual performance in Sukoharjo Pratama Tax Service Office. The research was done through filling the questionnaires by the tax services office employees Sukoharjo Pratama, sample taken as many as 64 respondents. Analitycal techniques used was multiple linear regression analysis. The results of study indicate that information technology, utilization of information technology, and confidence in information technology influence on individual performance. While usage effectiveness the variable has no effect on individual performance. Keywords : information technology, utilization of information technology, usage effectiveness, confidence in information technology, individual performance